Metabolic Symbiosis in Chemoresistance: Refocusing the Role of Aerobic Glycolysis - Ma, Lisi; Zong, Xiangyun (Frontiers in Oncology, 2020)
Abstract: Cellular metabolic reprogramming is now recognized as a hallmark of tumors. Altered tumor metabolism determines the malignant biological behaviors and phenotypes of cancer. More recently, studies have begun to reveal that cancer cells generally exhibit increased glycolysis or oxidative phosphorylation (OXPHOS) for Adenosine Triphosphate（ATP）generation, which is frequently associated with drug resistance. The metabolism of drug-resistant cells is regulated by the PI3K/AKT/mTOR pathway which ultimately confer cancer cells drug resistance phenotype. The key enzymes involved in glycolysis and the key molecules in relevant pathways have been used as targets to reverse drug resistance. In this review, we highlight our current understanding of the role of metabolic symbiosis in therapeutic resistance and discuss the ongoing effort to develop metabolic inhibitors as anti-cancer drugs to overcome drug resistance to classical chemotherapy.